Thin and low‐reflection metal black matrix for high ppi liquid crystal display. Issue 5 (19th April 2022) - Yoshida, Keisuke; Ueda, Satoshi; Hachiya, Atsushi; Okada, Kuniaki; Hirai, Akira; Kawahira, Yuichi; Misaki, Katsunori; Furukawa, Hiroaki; Katoh, Hiromi
Abstract: A 2.9‐inch 2K2K (1058 ppi) panel using low‐reflection metal black matrix (BM) has been developed. We confirmed lower reflectance of LCD with low‐reflection metal BM that is required for VR headsets recently and also confirmed that there was no adverse effect on the display optical characteristics. We have shown that a thinner BM allows us to design more transparent pixels by increasing the aperture ratio or to increase the color viewing angle. Abstract : A 2.9‐inch 2K2K (1058 ppi) panel using low‐reflection metal black matrix (BM) has been developed. We confirmed lower reflectance of LCD and also confirmed that there was no adverse effect on the characteristics. We have shown that a thinner BM which is low‐reflection metal BM allows us to design frexibility.